Noninvasive Diagnosis of Visceral Leishmaniasis: Development and Evaluation of Two Urine-Based Immunoassays for Detection of Leishmania donovani Infection in India. - Sarfaraz Ahmad Ejazi; Pradyot Bhattacharya; Md Asjad Karim Bakhteyar; Aquil Ahmad Mumtaz; Krishna Pandey; Vidya Nand Ravi Das; Pradeep Das; Mehebubar Rahaman; Rama Prosad Goswami; Nahid Ali (Public Library of Science (PLoS), 2016)
Visceral Leishmaniasis (VL), a severe parasitic disease, could be fatal if diagnosis and treatment is delayed. Post kala-azar dermal leishmaniasis (PKDL), a skin related outcome, is a potential reservoir for the spread of VL. Diagnostic tests available for VL such as tissue aspiration are invasive and painful although they are capable of evaluating the treatment response. Serological tests although less invasive than tissue aspiration are incompetent to assess cure. Parasitological examination of slit-skin smear along with the clinical symptoms is routinely used for diagnosis of PKDL. Therefore, a noninvasive test with acceptable sensitivity and competency, additionally, to decide cure would be an asset in disease management and control.We describe here, the development of antibody-capture ELISA and field adaptable dipstick test as noninvasive diagnostic tools for VL and PKDL and as a test of cure in VL treatment. Sensitivity and specificity of urine-ELISA were 97.94% (95/97) and 100% (75/75) respectively, for VL. Importantly, dipstick test demonstrated 100% sensitivity (97/97) and specificity (75/75) in VL diagnosis. Degree of agreement of the two methods with tissue aspiration was 98.83% (κ = 0.97) and 100% (κ = 1), for ELISA and dipstick test, respectively. Both the tests had 100% positivity for PKDL (14/14) cases. ELISA and dipstick test illustrated treatment efficacy in about 90% (16/18) VL cases when eventually turned negative after six months of treatment.ELISA and dipstick test found immensely effective for diagnosis of VL and PKDL through urine samples thus, may substitute the existing invasive diagnostics. Utility of these tests as indirect methods of monitoring parasite clearance can define infected versus cured. Urine-based dipstick test is simple, sensitive and above all noninvasive method that may help not only in active VL case detection but also to ascertain treatment response. It can therefore, be deployed widely for interventions in disease management of VL particularly in poor resource outskirts.